The impact of transportation on commercial activities: The stories of various transport routes in Changchun, China. (January 2023) - Ma, Zuopeng; Li, Chenggu; Zhang, Pingyu; Zhang, Jing; Liu, Daqian; Xie, Mingke
Abstract: Understanding the differences in the commercial landscape-shaping ability of various transport routes is important in proactive urban planning and achieving joint development. This study probes which type of transport routes (expressways, rail transit and trunk roads) is more closely associated with which type of commercial activities (retail, wholesale, auto service, catering, finance and recreation). At the city-wide scale, the density of rail transit is highly correlated with the locations of catering, retail, and recreation establishments. Among the three types of activities, catering exhibits the highest correlation with rail transit, retail the next and recreation last. Expressway density is significantly correlated with the locations of recreation, automobile service, and wholesale activities and its correlations increase in turn. The density of trunk roads is positively related to the locations of auto service, wholesale, and finance activities and that correlations increase sequentially. At the microscale, expressways, trunk roads and rail transit exhibit various corridor effects on locational selection of different types of commercial activities, and the strength of the corridor effect is contingent on the type of transport routes. Highlights: The research explore the differences in commercial landscape-abilities of different types of transport routes from two perspective — at city-wide and corridor scales. We explore which type of transport routes is more closely correlated with which type of density of commercial activities at city-wide scale. We compared the strength of corridor effects of different types of transport routes on commercial establishments.